2015
DOI: 10.1111/eea.12263
|View full text |Cite
|
Sign up to set email alerts
|

Development of Clitoria ternatea as a biopesticide for cotton pest management: assessment of product effect on Helicoverpa spp. and their natural enemies

Abstract: The Australian cotton industry is now dominated by transgenic (Bt) varieties, which provide a strong platform for integrated pest management (IPM) of Helicoverpa spp. (Lepidoptera: Noctuidae). New IPM‐compatible tools are required to manage the development of resistance in Helicoverpa spp. and the control of other sucking pests. A 10‐year study commenced in 2001 to identify short‐range, non‐volatile compounds on organ surfaces of plants that deter feeding or oviposition, or are toxic and do not support develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 30 publications
0
8
0
2
Order By: Relevance
“…Expanding on the initial findings of Poth et al (2011a), additional studies have reported pesticidal activities of cyclotide extracts from C. ternatea (Gilding et al, 2015; Mensah et al, 2015) (Table 5). Gilding et al (2015) showed that C. ternatea extracts permeabilized insect-like membrane lipids, with the shoot extracts exhibiting the greatest potency (0.31 μg/mL LC 50 ).…”
Section: Historical and Current Applicationsmentioning
confidence: 96%
See 1 more Smart Citation
“…Expanding on the initial findings of Poth et al (2011a), additional studies have reported pesticidal activities of cyclotide extracts from C. ternatea (Gilding et al, 2015; Mensah et al, 2015) (Table 5). Gilding et al (2015) showed that C. ternatea extracts permeabilized insect-like membrane lipids, with the shoot extracts exhibiting the greatest potency (0.31 μg/mL LC 50 ).…”
Section: Historical and Current Applicationsmentioning
confidence: 96%
“…Another study reported that application of oil-based C. ternatea mixture (1–2% v/v) to transgenic and conventional cotton crops, resulted in Helicoverpa spp. larval mortality and reduced oviposition and larval feeding (Mensah et al, 2015). Detrimental effects of the extract against beneficial insects were not observed (Mensah et al, 2015), suggesting that C. ternatea extracts could provide the basis for eco-friendly natural insecticides.…”
Section: Historical and Current Applicationsmentioning
confidence: 99%
“…Hal ini karena adanya kandungan antosianin yang menghasilkan warna biru (Suebkhampet & Sotthibandhu, 2012). Selain itu, tanaman ini juga dimanfaatkan sebagai pakan ternak (Sutedi, 2013;Morsy & Awadalla, 2017) dan fungisida (Mensah, Leach, Young, Watts, & Glennie, 2015;Suganda & Adhi, 2017). Oleh karena itu, tanaman bunga telang memiliki potensi untuk dikembangkan.…”
Section: Pendahuluanunclassified
“…En Australie, un produit à base d'huile de Clitoria ternatea (Fabaceae) est utilisé pour son effet dissuasif sur l'oviposition et l'alimentation des larves d'Helicoverpa spp. (Mensah et al, 2015). L'utilisation de médiateurs chimiques ou substances sémiochimiques régissant les relations plantes-insectes constitue une voie en plein essor.…”
Section: Lutte Biotechniqueunclassified